2012
DOI: 10.1016/j.nbd.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The mismatch repair system protects against intergenerational GAA repeat instability in a Friedreich ataxia mouse model

Abstract: Friedreich ataxia (FRDA) is an autosomal recessive neurodegenerative disorder caused by a dynamic GAA repeat expansion mutation within intron 1 of the FXN gene. Studies of mouse models for other trinucleotide repeat (TNR) disorders have revealed an important role of mismatch repair (MMR) proteins in TNR instability. To explore the potential role of MMR proteins on intergenerational GAA repeat instability in FRDA, we have analyzed the transmission of unstable GAA repeat expansions from FXN transgenic mice which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
5
61
2
Order By: Relevance
“…Several studies have pointed to the involvement of MutS␤ (MSH2/MSH3) in triplet-repeat instability in transgenic mice (8,15,39). Our previous ChIP assays (16) also show that at a resolution of ϳ1 kb, there is an increased occupancy of MSH2 and MSH3 downstream of the GAA⅐TTC triplet repeats in FRDA iPSCs compared with an unaffected iPSC line, but, in contrast, not 1254 bp upstream of the FXN transcriptional start site or directly upstream of the GAA⅐TTC triplet repeats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have pointed to the involvement of MutS␤ (MSH2/MSH3) in triplet-repeat instability in transgenic mice (8,15,39). Our previous ChIP assays (16) also show that at a resolution of ϳ1 kb, there is an increased occupancy of MSH2 and MSH3 downstream of the GAA⅐TTC triplet repeats in FRDA iPSCs compared with an unaffected iPSC line, but, in contrast, not 1254 bp upstream of the FXN transcriptional start site or directly upstream of the GAA⅐TTC triplet repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cell models using a plasmid construct with GAA⅐TTC triplet repeats have shown that the repeat expansions are transcription-, replication-, and position-dependent (10 -12). In addition, mouse models with expanded GAA⅐TTC triplet repeats show somatic instability in different tissues (13)(14)(15). These systems differ substantially from humans and from each other in terms of DNA replication rate, the cell type in which GAA⅐TTC triplet-repeat expansion occurs, and chromatin structure.…”
mentioning
confidence: 99%
“…The mismatch repair proteins MSH2, MSH3, MLH1, MLH3, and PMS2 have all been shown to modulate TNR instability in mouse models with CAG, CTG, GAA, and CGG expansions [21,[29][30][31][32][33][34][35][36][37][38][39][50][51][52][53]. In addition, MSH6 is involved in GAA repeat instability but appears to have little effect on CAG/CTG instability [35,38,[51][52][53].…”
Section: ) Variations In the Stoichiometry Of Dna Repair Proteins Acmentioning
confidence: 99%
“…In addition, MSH6 is involved in GAA repeat instability but appears to have little effect on CAG/CTG instability [35,38,[51][52][53]. These results prompted a systematic investigation of the levels of MSH2, MSH3 and MSH6 in several murine tissues [54], but no obvious correlation was found between instability phenotypes and protein levels.…”
Section: ) Variations In the Stoichiometry Of Dna Repair Proteins Acmentioning
confidence: 99%
“…Recently however, it was determined that knockdown of MSH2 in FRDA patient-derived induced pluripotent stem cells (iPSCs) caused a slower rate of GAA⅐TTC expansion (26). Furthermore, it has also been reported that the MMR system plays a role in intergenerational GAA⅐TTC repeat dynamics in an FRDA mouse model (27). Thus it appears that regardless of the ability of a particular trinucleotide sequence to form hairpin structures, the contribution of DNA mismatch repair may be a common denominator in TNR expansion disorders.…”
mentioning
confidence: 99%